Glial cell crosstalk in the local microenvironment following spinal cord injury - Erliang Li; Yingchao Gao; Jianfeng Zhang; Peng Zou; Huanhuan Qiao; Rui Zhang; Yansheng Huang (Brain Research Bulletin)
Spinal cord injury (SCI) has a high incidence, significant rates of disability, and substantial economic costs. The response of glial cells is crucial for spinal cord regeneration following SCI. However, the roles of various glial cell types in SCI pathology and their interactions with other cellular targets remain poorly understood. Using single-cell RNA sequencing, we characterized the local microenvironment following SCI and isolated three glial cell types—microglia, astrocytes, and oligodendrocytes—at the injury site. Immunofluorescence confirmed the differential expression of these cell types in spinal cord tissues. Four subtypes of microglia were identified: activated, dividing, homeostatic, and inflammatory. Astrocytes were categorized into 11 clusters, while oligodendrocytes were classified into eight clusters. Enrichment analysis indicated that the loss of oligodendrocytes was associated with ferroptosis. The glial cell crosstalk network revealed various interactions, including TIMP1-FGFR2 and PLXNB2-PTN in astrocytes and oligodendrocytes, as well as LGALS3-MERTK, GPR37L1-PSAP, TFRSF1A-GRN, and PGRMC2-CCL4L2 in astrocytes and microglia. A total of 75 drugs were identified through target-drug screening. This study suggests potential differentiation and intricate crosstalk among these three cell types, provides a theoretical framework for simulating the glial cellular microenvironment of SCI, and establishes a foundation for future interventions aimed at targeting various glial cell processes in the treatment of SCI.